(untitled) (PerCursos, 2023)
The demographic changes that Brazil has gone through evoke from society a set of actions aimed at a better adaptation to this new reality. In this article, which is an cutout of the dissertation “The place of old age in the education of EJA teachers: an analysis of gerontological beliefs, attitudes and knowledge”, we seek to identify the scenario of international scientific productions that deal with the training of teachers for with the elderly public. The interest in observing the international reality was due to the understanding that the demographic changes that are increasingly evident in Brazil today, have already been perceived in other places, in different periods and cadences. For this purpose, a scoping review was carried out based on the Educational Resources Informations Center and the Web of Science. Altogether, we obtained a total of five articles, from different nationalities, which worked, in general, based on three concepts: Lifelong Learning; Gerontology; Educational gerontology. As highlights perceived in the joint analysis of these articles, we realized that there is a need for specific training to work with the elderly public. It was also identified that training for acting with adults and the elderly has not been appearing as a priority agenda on the part of public policies for teacher training. The articles also indicate the prevalence of the association of old age with negative stereotypes. Finally, we also show that the appreciation of the student’s experience is a basic element for the realization of a quality education.